Alteration in Vital State Parameters of Scots Pine Tree-Stands under Technogenic Pollution - Mikhailova, Tatiana A.; Kalugina, Olga V.; Shergina, Olga V.; Taranenko, Ekaterina N. (International Journal of Environment, 2014)
The study was focused on the relation between deterioration of vital state parameters of Scots pine (Pinus sylvestris L.) tree-stands polluted by various technogenic sources, and the level of polluting agents accumulation in the needles. Changes in the balance of the most important biogenic elements and their proportion in the needles of polluted trees have been shown. The results confirm systemic character of polluting agents impact on tree-stands vital state. It may be presumed to show in the following order: polluting agents accumulation in assimilating organs → disbalance of elements composition of plant organism → disturbance of plant organism nutritious conditions → disturbance of tree growth characteristics → reduction of tree-stands productivity. DOI: http://dx.doi.org/10.3126/ije.v3i4.11729 International Journal of Environment Volume-3, Issue-4, Sep-Nov 2014 Page: 36-43